HUBUNGAN STRES DAN KECEMASAN DENGAN KEJADIAN INSOMNIA PADA PERAWAT SELAMA PANDEMI COVID-19 - Rahmat, Rahmat Kurniawan; Evie, Sova; Supriadi B., Supriadi B.; Nurmiaty, Nurmiaty; Khotimah, Siti Kusnul; Saripah, Eli; Isran; T. Iskandar Faisal, Iskandar; Nuswatul Khaira, Khaira; Hasan, Sri Musriniawati; Sukmawati (Jurnal Keperawatan Muhammadiyah, 2026)
Introduction: The increase in COVID-19 cases has put nurses under pressure. This condition can affect the stress and anxiety levels of nurses in treating patients. Stress can cause sleep disturbances, such as insomnia. Research objective: To determine the relationship between stress and anxiety and the incidence of insomnia among nurses during the COVID-19 pandemic at the South Tangerang City General Hospital. Research Method: A cross-sectional study was conducted to determine the relationship between independent and dependent variables. Data were collected using questionnaires. A total of 84 nurses at the South Tangerang City General Hospital were sampled using simple random sampling. Research Results: The characteristics of the respondents based on age showed that almost half of the respondents were aged 30-39 years old (38 people or 45.8%), most of the respondents were female (62 people or 73.8%), more than half of the respondents had a D3 nursing education (53 people or 63.1%), almost half of the respondents had been working for 3-5 years (38 people or 45.2%), more than half of the respondents experienced insomnia (62 people or 73.8%), more than half of the respondents had moderate stress levels (44 people or 52.4%), and almost half of the respondents had moderate anxiety levels (32 people or 38.1%). Statistical test results showed stress levels with a p-value of 0.000 and anxiety levels with a p-value of 0.029 (alpha <0.05). Conclusion: There is a relationship between stress and anxiety and the occurrence of insomnia among nurses during the COVID-19 pandemic at the South Tangerang City General Hospital.